Can gains from early literacy interventions be sustained? The case of Reading Recovery. (8th October 2013) - Jesson, Rebecca; Limbrick, Libby
<x xml:space="preserve">Abstract</x> Early literacy interventions have demonstrated that pedagogically sound programmes can boost reading achievement for students who do not succeed in early literacy learning. However, there is less evidence as to what extent gains are maintained in subsequent years or the factors which may contribute to sustained progress. The research reported in this article employed a cross‐sectional design to investigate the achievement of students who had previously participated in Reading Recovery. Two to four years after successfully completing the intervention, students were assessed in reading and writing by using standardised assessment tools. Although 60% of students had retained parity in reading in comparison with their age cohort, 40% were markedly below the mean of the cohort and the national norm. Data from case study schools provide some initial suggestions for school implementation factors which affect continued success. Conclusions regarding the need to plan for sustainability of gains following early intervention are made.